Numerical and experimental study of VM type pulse tube cryocooler with multi-bypass operating below 4 K. (March 2019) - Pan, Changzhao; Wang, Jue; Luo, Kaiqi; Chen, Liubiao; Jin, Hai; Cui, Wei; Wang, Junjie; Zhou, Yuan
Highlights: The mechanism of multi-bypass was numerical studied. Multi-bypass has the functions of orifice and double-inlet, making it like two-stage cryocooler. A minimum no-load temperature 3.7 K was obtained, and the cooling power was 14 mW@4.2 K. New mK cooling chain for HUBS satellite was proposed and analyzed. Abstract: The Vuilleumier (VM) type pulse tube cryocooler (VPTC) is a new kind of 4 K cryocooler which had been experimentally verified. This paper presents the recent advances on a 4 K VPTC in our laboratory. First, the mechanism of multi-bypass was numerically studied using Sage software. The results showed that the function of the multi-bypass is not only similar to a double-inlet, but also to an orifice, which makes the VPTC work like a two-stage cryocooler. Based on the simulation results, the performance of VPTC was experimentally studied. Under its optimal operating conditions, a no-load temperature of 3.7 K has been obtained, which is the first demonstration of a single-stage VPTC obtaining temperatures below 4 K. It can supply about 14mW cooling power at 4.2 K and about 100 mW cooling power at 35 K simultaneously, which has potential application as the pre-cooler for an adiabatic demagnetization refrigerator (ADR). Finally, based on this VPTC, a new mK cooling chain for HUBS (Hot Universe Baryon Surveyor) satellite is proposed and its prospect has also been theoretically analyzed.